Correction to: Jurisdiction shopping and foreign location choice: The role of market and nonmarket experience in the European solar energy industry - Georgallis, Panikos; Albino-Pimentel, João; Kondratenko, Nina (Journal of International Business Studies, 2021)
The original version of this paper was inadvertently published with errors in the author names. The correct author names are Panikos Georgallis, João Albino-Pimentel and Nina Kondratenko.